A visit to the information mall: Perspectives on students’ navigation of the world wide web / Abrizah Abdullah, N.N.Edzan and A.N. Zainab - Abdullah, Abrizah; N.N., Edzan; A.N., Zainab (2004)
This study concentrates on the general web-based information seeking behaviour of secondary school students and their use of websites, in particular, finding if Secondary Three students use Web resources for their information needs in conducting school projects and assignments. The survey aimed to discover the level of Internet searching ability and problems encountered. It was an effort of an initial fact-finding process to investigate students’ readiness and reception to usage of digital libraries. As confident and savvy Internet users, the sample surveyed value access to accurate, up-to-date information accessed in the shortest time possible. They are aware of the shortcomings of information available from the Web and of their needs for assistance in conceptualizing search terms.